2020
DOI: 10.1002/14651858.cd012977.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for escalation of therapy for acute exacerbations of asthma in children: an overview of Cochrane Reviews

Abstract: Interventions for escalation of therapy for acute exacerbations of asthma in children: an overview of Cochrane Reviews.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 80 publications
0
33
0
2
Order By: Relevance
“…However, in 85% of children receiving escalated therapy with intravenous bronchodilator treatment, this was confined to just three different regimens; intravenous magnesium alone or in combination with either aminophylline or salbutamol. Once again, the lack of high-quality evidence,15 as well as inconsistent local guidelines, may contribute to this variation. While magnesium and salbutamol are listed as second-line and third-line bronchodilators for management of acute severe paediatric asthma in Australian national guidelines,27 some state-based guidelines prefer magnesium and aminophylline 28.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in 85% of children receiving escalated therapy with intravenous bronchodilator treatment, this was confined to just three different regimens; intravenous magnesium alone or in combination with either aminophylline or salbutamol. Once again, the lack of high-quality evidence,15 as well as inconsistent local guidelines, may contribute to this variation. While magnesium and salbutamol are listed as second-line and third-line bronchodilators for management of acute severe paediatric asthma in Australian national guidelines,27 some state-based guidelines prefer magnesium and aminophylline 28.…”
Section: Discussionmentioning
confidence: 99%
“…Cochrane reviews of advanced pharmacologic treatment of children with acute exacerbations of asthma highlight a number of knowledge gaps 15. The evidence supporting intravenous magnesium is extremely limited (including only 5 studies and 182 children),31 while only one study (showing no significant benefit) was identified regarding intravenous ketamine 32.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultimately, AAEs in children remain a significant burden on children’s health and substantial work is required to improve the care of children with AAEs. Identified directions for continued growth include 6 , 7 , 11 , 61 , 97 higher quality studies on ideal dosing, duration, and efficacy of existing pharmacotherapies and mechanical ventilation (particularly with critical AAEs) targeting outcomes such as hospitalization rates and including data from diverse populations; increased understanding of adverse drug events and developmental impacts of AAE; novel pharmacotherapies; strategies to deliver equitable care for children from identified racial minority and disadvantaged socioeconomic backgrounds; improved knowledge translation and implementation of AAE pathways; and improved integration of AAEs and long-term asthma care approaches.…”
Section: Discussionmentioning
confidence: 99%
“…If more than four domains were regarded as unclear or no, the study was deemed as having a high risk of bias. The study was regarded as having a moderate risk of bias if two or three domains were considered no or unclear [18]. Review Manager 5.3 (Cochrane Collaboration, Oxford, UK) was used to carry out the quality assessment and investigation of publication bias.…”
Section: Data Extraction and Qualitymentioning
confidence: 99%